(untitled) (Sustainable Construction (SUSCON), 2024)
The purpose of this study is to determine the side barriers on the Ahmad Yani road The results of this study were carried out by direct observation at the research location The research results show that the highest traffic volume occurs in the afternoon in passenger car units pcu hour the highest traffic flow is obtained on Tuesday at 15 00 16 00 at 2938 2 pcu hour The highest calculated side barriers are on Tuesdays at 15 00 16 00 in 1 hour namely 513 9 events hour which is included in the High H side resistance class so that the total value of the degree of saturation is 0 9832 where the level of service E The flow is unstable the volume is close to capacity the speed is low and sometimes stops Based on the problem of side obstacles the way that needs to be done is to make regulations in the form of a prohibition against parking carelessly on the road especially on the side of the road by providing sanctions for those who violate it as well as making road markings and special signs for pedestrians < p>